IMPLEMENTATION OF INDIVIDUALIZED EDUCATION PROGRAMS (IEP) TO IMPROVE LEARNING OUTCOMES FOR INCLUSIVE STUDENTS IN THE MERDEKA CURRICULUM AT ELEMENTARY SCHOOLS - Fadhilatun Ni'mah,; Rodliyatin Ni’am, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Inclusive education is a solution to the existence of barriers in the world of education that differentiate between normal children and children with special needs. This study uses qualitative research with a case study approach. The data were obtained through interviews and observations to get data on the implementation of IEP in improving the learning outcomes of inclusive students. The results of this study indicate that implementing IEP can improve the learning outcomes of inclusive students. This IEP describes the planning, implementation, and evaluation stages. The planning stage in implementing IEP includes an initial assessment by experts, meetings with parents to present the assessment results, and compiling IEP. The implementation stage begins with a presentation carried out by the GPK, practice, and supervision, divided into two parts, namely indoor and outdoor learning and independent practice, in the form of assignments that have been adjusted to IEP. The evaluation stage is divided into daily, weekly, and monthly evaluations. This study shows the importance of IEP in supporting student learning success because it is adjusted to their needs. The conclusion of this study is the importance of implementing IEP in improving the learning outcomes of inclusive students who are adjusted to the Merdeka curriculum.